Experience and measurement of fatigue in adults with Crohn's disease: results from qualitative interviews and a longitudinal 2-week daily diary pilot study - Miguel Regueiro; Laure Delbecque; Theresa Hunter; Larissa Stassek; Gale Harding; James Lewis (SpringerOpen, 2023)
Abstract Background Fatigue has a detrimental impact on health-related quality of life and functioning in patients with Crohn's disease (CD). We aimed to confirm the relevance and importance of fatigue, establish the content validity of the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), qualitatively explore meaningful change in fatigue experience, and assess the measurement properties of the FACIT-F in patients with moderate-to-severe CD. Methods This was a mixed-methods observational study consisting of a cross-sectional qualitative interview (Part A) and a longitudinal 2-week daily diary pilot study (Part B) in participants aged ≥ 18 years with a clinical diagnosis of moderate-to-severe CD. Part A included open-ended questions related to the participant's overall experiences with CD, fatigue, and impact on daily activities and a cognitive debriefing of several patient-reported outcomes (PROs), including the FACIT-F. Part B consisted of participants completing an electronic daily diary that included the FACIT-F and other PROs for 14 days. Item performance, test-retest reliability, and construct validity were assessed at baseline (Day 1), Day 7, and Day 14. Results Thirty-five participants (mean age 45.1 years; 65.7% female) completed an interview (Part A). Ninety-one percent of the interview participants reported fatigue as a symptom attributed to CD. Participants indicated that fatigue had a major impact on their daily activities (e.g., recreation/ hobbies, work/school, yard work and housework), social activities, and emotional health. The FACIT-F was well understood by the interview participants. Seventy-six participants (mean age 41.9 years; 66% female) completed at least the Day 1 diary entry (Part B). Potential floor and ceiling effects were observed for several FACIT-F items, but test-retest reliability and construct validity were all strong and within the ranges hypothesized a priori. Conclusions The interviews indicate that fatigue is a frequent and bothersome symptom experienced by most patients with moderate-to-severe CD and support the content validity of the FACIT-F in this population. Daily diary study results indicate that the FACIT-F scale demonstrates adequate reliability and validity among patients with CD. These study findings suggest that the FACIT-F would be a reliable, valid, and useful measure of fatigue in patients with moderate-to-severe CD.